Severity of respiratory failure and computed chest tomography in acute COVID-19 correlates with pulmonary function and respiratory symptoms after infection with SARS-CoV-2: An observational longitudinal study over 12 months. (January 2022) - Steinbeis, Fridolin; Thibeault, Charlotte; Doellinger, Felix; Ring, Raphaela Maria; Mittermaier, Mirja; Ruwwe-Glösenkamp, Christoph; Alius, Florian; Knape, Philipp; Meyer, Hans-Jakob; Lippert, Lena Johanna; Helbig, Elisa Theresa; Grund, Daniel; et al.
Abstract: Introduction: Prospective and longitudinal data on pulmonary injury over one year after acute coronavirus disease 2019 (COVID-19) are sparse. We aim to determine reductions in pulmonary function and respiratory related quality of life up to 12 months after acute COVID-19. Methods: Patients with acute COVID-19 were enrolled into an ongoing single-centre, prospective observational study and prospectively examined 6 weeks, 3, 6 and 12 months after onset of COVID-19 symptoms. Chest CT-scans, pulmonary function and symptoms assessed by St. Georges Respiratory Questionnaire were used to evaluate respiratory limitations. Patients were stratified according to severity of acute COVID-19. Results: Median age of all patients was 57 years, 37.8% were female. Higher age, male sex and higher BMI were associated with acute-COVID-19 severity (p < 0.0001, 0.001 and 0.004 respectively). Also, pulmonary restriction and reduced carbon monoxide diffusion capacity was associated with disease severity. In patients with restriction and impaired diffusion capacity, FVC improved over 12 months from 61.32 to 71.82, TLC from 68.92 to 76.95, DLCO from 60.18 to 68.98 and KCO from 81.28 to 87.80 (percent predicted values; p = 0.002, 0.045, 0.0002 and 0.0005). The CT-score of lung involvement in the acute phase was associated with restriction and reduction in diffusion capacity in follow-up. Respiratory symptoms improved for patients in higher severity groups during follow-up, but not for patients with initially mild disease. Conclusion: Severity of respiratory failure during COVID-19 correlates with the degree of pulmonary function impairment and respiratory quality of life in the year after acute infection. Graphical abstract: Image 1 Highlights: Adverse pulmonary outcome is associated with initial COVID-19 disease severity. Pulmonary restriction and reduced DLCO are the main pulmonary sequelae after COVID-19. Pulmonary restriction at follow-up correlates with initial COVID-19 disease severity. Quality of life remains compromised in patients even with initially mild COVID-19.